Building Customer Engagement Through User-Generated Content: A Case Study on @Bt21Stuff.Id - Aimee Anindya Putri; Elke Alexandrina (Journal of Research on Business and Tourism, 2022)
As the popularity of K-Pop culture increases rapidly in Indonesia, many people started to see this as an opportunity to start a business. The business which started to get popular amongst K-Pop fans community nowadays is an online shopping entrusted goods service business which specialized in providing a service to help K-Pop fans in purchasing their favorite idol merchandises directly from South Korea. The competition for this online shopping entrusted goods service business keeps growing and increases every day, due to the popularity of K-Pop and the customers plays a crucial role in this business. Therefore, maintaining a customer engagement for this business is very necessary. The objective of this research is to reveal the contribution of user generated content created by the customers as a way to build customer engagement of @bt21stuff.id and also to reveal the motivations behind the creation of user generated content by the customers. This research is using a qualitative methodology and guided by using the concept of customer engagement cycle by Sashi (2012). The findings of this research shows that the user generated content plays a role in each stage of the customer engagement cycle and that the customers are mostly motivated by the empowerment motives in creating the user generated content.